Interference Management in LTE Femtocell Systems Using an Adaptive Frequency Reuse Scheme - Christos Bouras; Andreas Papazois; Vasileios Kokkinos; Georgios Kavourgias (Wireless Telecommunications Symposium (WTS 2012), London, UK, 2012)
Long Term Evolution (LTE) has developed a new technology in order to enhance indoor coverage. This new technology is called femtocells and is achieved with the use of access points installed by home users. However, interference problem between the femtocell and the macrocell decreases the system's capacity and as a result users' throughput. In this paper we study the interference mitigation techniques in femtocell/macrocell networks and we propose a frequency reuse mechanism that leads to increased overall system performance. In particular, the mechanism aims to maximize throughput via a variety of combinations between inner cell radius and frequency allocation to the macrocell. Additionally, a position minded frequency allocation to the femtocells targets to further optimize the total throughput of the cell.
Keywords: Femtocell; FFR; LTE